Dikili dan Tolangga: Nilai-Nilai Bimbingan dan Konseling Islam dalam Tradisi Masyarakat Pelita Jaya Bone Raya Gorontalo (Jurnal Bimbingan dan Konseling Islam, 2021)
Walimah as a tradition of the Gorontalo community certainly has its own meaning or value in its implementation. This study aims to integrate and explore the values of Islamic guidance and counseling in the walimah tradition. This study uses a qualitative method with a phenomenological approach. Data obtained from interviews, observations, and documentation. The results of this study conclude that there are Islamic guidance and counseling values in the walimah tradition of the Gorontalo community including personal values, social values, religious values, compassion values, the value of happiness in the world and the hereafter, the value of physical-spiritual unity, the value of education, and the value of deliberation.